Pemanfaatan Citra Landsat Untuk Estimasi Indeks Spektral Vegetasi di Wilayah Kuta, Kuta Utara, dan Kota Denpasar - Fernando, Fernando; Diara, I Wayan; Suyarto, R. (Nandur, 2023)
The declining amount of carbon stock occurs due to the reduction of aboveground biomass, the increase in population, and the development of urban development. This study aims to analyze changes in the spatial distribution of vegetation index, carbon stock distribution, and biomass carbon stock every 5 years from 2002 to 2022 in Kuta, North Kuta, and Denpasar areas. The method used in this research is Image processing with Partial least square (PLS) model and random forest (RF). The data used in the study include Landsat images with recording in 2002, 2007, 2012, 2017 and 2022. The results of this study show that Kuta and Denpasar areas have different values and patterns of spectral index changes every 5 years for the vegetation index used. The area of change in the spatial distribution of carbon stocks increased every 5 years from vegetated to non-vegetated areas. The biomass carbon stock decreased over 20 years from very low, low, medium and high categories to non-vegetated. This condition occurs due to the development of built-up land in the tourism area of Kuta, North Kuta, and residential areas in Denpasar City.